Hybrid superconducting fault current limiting CORC® wires with millisecond response time. (7th February 2019) - Weiss, Jeremy D; Kim, Chul; Pamidi, Sastry; van der Laan, Danko C
Abstract: The extensive development of Conductor on Round Core (CORC ® ) cables and wires has resulted in round, multi-strand, high-temperature superconductors (HTS) with engineering critical current densities ( J e ) over 200 A mm −2 at 77 K, or over 800 A mm −2 at 50 K when cooled with cryogenic helium gas. The inherent fault current limiting (FCL) capabilities during direct current operation of a short kA-class CORC ® wire of less than 4 mm in diameter are demonstrated in liquid nitrogen, developing nearly instantaneous voltages in excess of 20 V m −1 that increased to about 70 V m −1 within 15 ms of applied overcurrents up to 250% of the critical current ( I c ). The CORC ® wire response time and reactive voltage is comparable to that of a single tape, but at a much higher critical current and without the risk of burnout. The performance of the 0.15 m long CORC ® wire remained unchanged after close to 100 overcurrent events with peak dissipation of 150–190 kW m −1 . Each event in which a total energy up to 1.4 kJ m −1 was dissipated in the CORC ® wire resulted in a rapid heating followed by a subsequent thermal quench. The significant challenge to remove the heat from the FCL cable after a fault has cleared when cooled with helium gas in future naval power cables is addressed. Operation of the CORC ® FCL conductor in stand-alone operation and operated as part of a hybrid-cable system, in which the overcurrent is instantly redirected to a normal conducting path outside of the cryogenic environment, is demonstrated without any degradation of the CORC ® wire performance. The results show that highly flexible CORC ® wires offer a straightforward path to safely increasing the operating current of FCL conductors beyond that of single tapes, without compromising their response time and voltage, while potentially allowing fast recovery times even when cooled with cryogenic helium gas.